Fertility awareness-based methods of family planning. (July 2020) - Simmons, Rebecca G.; Jennings, Victoria
Abstract: Fertility awareness-based methods (FABMs) of family planning involve monitoring various signs and symptoms of fertility during the menstrual cycle to identify the "fertile window, " or the days of the cycle when unprotected intercourse is most likely to result in pregnancy. Signs and symptoms include menstrual cycle length, basal body temperature, urinary hormone measurements, and/or cervical fluid and may be used alone or in combination. Fertility signs reflect both physiological changes during the menstrual cycle and the life cycle of the ovum and sperm. Women learn to observe or measure and interpret these signs according to the instructions of their chosen FABM and avoid unprotected intercourse on fertile days. FABMs are appropriate for those who choose to use them, are able and willing to observe one or more fertility signs, and are in relationships that support the use of a coitus-related method such as a condom or abstaining from intercourse on fertile days. Highlights: FABMs are contraceptives where people use personal physiological data to determine their fertility and make decisions around sexual activity on fertile days. There are different FABMs; each collects different physiological information, each has separate rules for use, and each has different perfect- and typical-use pregnancy rates. There are many emerging fertility technologies, yet few have been subject to rigorous research around their contraceptive effectiveness.